Pathomorphological parameters of sepsis-associated encephalopathy in deceased septic patients without purulent lesions to the brain - Shulyatnikova, T. V.; Tumanska, L. M.; Шулятнікова, Тетяна Володимирівна; Туманська, Любов Михайлівна (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study was to specify the key pathomorphological parameters of sepsis-associated encephalopathy in deceased septic patients without purulent lesions to the brain by defining the changes of neurogliovascular unit and the level of tissue ammonia. Material and methods. Using pathohistological, histochemical, and immunohistochemical methods we studied cerebral cortex and white matter, hippocampus, thalamus, and cerebellum of 35 deceased septic patients with SAE in comparison with the control group, which included 30 patients who died from acute cardiovascular failure without CNS pathology. Results. In SAE, small foci of encephalolysis due to thrombosis of microvessels, ischemic-hypoxic and apoptotic changes in neurons are associated with the following parameters that are reliably (p < 0.05) different from the control group: higher (up to 199.48 %) level of tissue ammonia and increased number (up to 316.07 %) of caspase-3+ apoptotic neurons in the cortex, hippocampus, thalamus, and cerebellum; in all studied brain regions, an increased expression level of astrocytic glial fibrillary acidic protein (up to 192.69 %), glutamine synthetase (up to 134.41 %) and aquaporin-4 (up to 400.8 %); significant (up to 947.01 %) expansion of perivascular and pericellular “edematous” spaces, increased (up to 479.58 %) immunopositive area of extravascular CD68+ microgliocytes and increased (up to 374.43 %) proportion of CD68+ ameboid microgliocytes, increased (up to 3.66 times) number of Alzheimer type 2 astrocytes in cerebral cortex, thalamus, and cerebellum; increased (up to 2 times) number of amyloid bodies in the thalamus and cerebellum. Мета роботи – встановити основні патоморфологічні зміни нейрогліоваскулярного комплексу та рівня тка- нинного аміаку в головному мозку при сепсис-асоційованій енцефалопатії у померлих хворих на сепсис без гнійного ураження головного мозку. Матеріали і методи. Патогістологічними, гістохімічними, імуногістохімічними методами досліджено кору та білу речовину великих півкуль ГМ (ВПГМ), гіпокамп, таламус і мозочок 35 померлих хворих на сепсис і САЕ. Отримані показники порівняли з параметрами групи контролю, яка включала 30 померлих від гострої серцево-судинної недостатності пацієнтів без патології центральної нервової системи. Результати. При САЕ дрібні осередки енцефалолізису через тромбоз мікросудин, ішемічно-гіпоксичні й апоптотичні зміни нейронів у ГМ асоційовані з такими параметрами контрольної групи, що достовірно відрізнялися (p < 0,05): у корі ВПГМ, гіпокампі, таламусі та мозочку визначено вищий рівень (до 199,48 %) тканинного аміаку та більшу кількість (до 316,07 %) каспаза-3+ апоптотичних нейронів; у всіх досліджених відділах ГМ встановлено підвищений рівень експресії астроцитарного гліофібрилярного білка (до 192,69 %), глютамінсинтетази (до 134,41 %) та аквапорину-4 (до 400,8 %), значне (до 947,01 %) розширення перива- скулярних і перицелюлярних «набрякових» просторів, більшу площу (до 479,58 %) експресії позасудинних CD68+ мікрогліоцитів і більшу частку (до 374,43 %) CD68+ амебоїдних мікрогліоцитів; у корі ВПГМ, таламусі та мозочку зафіксовано більшу кількість (до 3,66 раза) астроцитів Альцгеймера 2 типу; у таламусі та мозочку встановлено більшу кількість (до 2 разів) амілоїдних тілець.
Патоморфологічні параметри сепсис-асоційованої енцефалопатії в померлих хворих на сепсис без гнійного ураження головного моз
Shulyatnikova T. V. - ORCID ID: 0000-0002-0196-9935; Tumanska L. M. - ORCID ID: 0000-0001-5715-0040.
Keywords: sepsis-associated encephalopathy; sepsis-associated liver injury; neuropathology; immunohistochemistry; ammonia; Alzheimer type 2 astrocytes; microglia; amyloid bodies; сепсис-асоційована енцефалопатія; сепсис-асоційоване пошкодження печінки; патоморфологія; імуногістохімія; аміак; астроцити Альцгеймера 2 типу; амебоїдна мікроглія; амілоїдні тільця